METHODS FOR MODELING THE RESULTS OF SOCIOLOGICAL RESEARCH - Dovranova Mokhidil (Scholars Digest Publishing, 2025)
This article analyzes the theoretical foundations, practical significance and modern methods of modeling the results of sociological research. Through sociological modeling, the possibilities of identifying the internal structure of social phenomena and processes, analyzing the cause-and-effect dependencies between them and predicting social change are revealed. The study outlined the advantages of statistical, mathematical and computer models in working with sociological data. The article concludes with suggestions and recommendations on the possibilities of modeling approaches to be used in sociological research.
Keywords: Research, modeling, research results, statistical methods, applied research, scientific research.